2001
DOI: 10.1212/wnl.57.10.1862
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar mediation of the complexity of bimanual compared to unimanual movements

Abstract: The study corroborated clinical use of diadochokinesis tasks to test for aspects of cerebellar integrity. The data do not support the literature emphasizing basal ganglia mediation of this type of coordinated movement. Cerebellar medial and vermal regions (in connection with central nuclei) are proposed as the locus within the cerebellum for mediating complexity, that is, the effective integration of separate limb movements that proceed in an asynchronous but systematic fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 25 publications
1
48
1
2
Order By: Relevance
“…The latter hypothesis is supported by several lines of physiological evidence, in animals and humans, indicating that bimanual complex movements engage somewhat different neural systems in cortical (Gordon et al 1998;Kazennikov et al 1999;Jancke et al 2000;Toyokura et al 2002;Nair et al 2003) and subcortical (Wannier et al 2002) regions, as well as in the cerebellum (Tracy et al 2001). Furthermore, on the basis of the known somatotopy of the motor cortex and cerebellum (Rijntjes et al 1999;Kurth et al 2000;Beisteiner et al 2001), the size of networks involved in controlling movements appears to vary as a function of the number of digits used in task performance.…”
Section: Differential Degrees Of Improvement and Motor Skill Complexitymentioning
confidence: 86%
“…The latter hypothesis is supported by several lines of physiological evidence, in animals and humans, indicating that bimanual complex movements engage somewhat different neural systems in cortical (Gordon et al 1998;Kazennikov et al 1999;Jancke et al 2000;Toyokura et al 2002;Nair et al 2003) and subcortical (Wannier et al 2002) regions, as well as in the cerebellum (Tracy et al 2001). Furthermore, on the basis of the known somatotopy of the motor cortex and cerebellum (Rijntjes et al 1999;Kurth et al 2000;Beisteiner et al 2001), the size of networks involved in controlling movements appears to vary as a function of the number of digits used in task performance.…”
Section: Differential Degrees Of Improvement and Motor Skill Complexitymentioning
confidence: 86%
“…The increased activation of the cerebellum is not surprising, because it is known to be involved in multilimb coordination (Debaere et al, 2001a(Debaere et al, , 2003Ramnani et al, 2001;Tracy et al, 2001;Meyer-Lindenberg et al, 2002;Ullen et al, 2003), and it becomes increasingly activated when coordination complexity rises (Ullen et al, 2003;Debaere et al, 2004). It has been hypothesized that cerebellar activity reflects increasing demands on motor timing (Ivry, 1997;Mima et al, 1999;Habas et al, 2004;Wenderoth et al, 2004b) and/or sensory processing (Jueptner et al, 1997;Bushara et al, 2001;Thickbroom et al, 2003).…”
Section: Coordination-specific Additional Activation In the Elderlymentioning
confidence: 99%
“…Cerebellar injury in humans has been shown to result in deficits in bimanual coordination (Brown et al, 1993;Serrien & Wiesendanger, 2000), and recent imaging studies revealed an activation of the cerebellum during bimanual movements (eg., Tracy et al, 2001, for more references, see the chapter of Wenderoth et al in this book). However, we are not aware of any single unit experiments that test for a cerebellar role in bimanual coordination.…”
Section: Which Brain Areas Are Involved In Bimanual Coordination?mentioning
confidence: 99%